Effects of Applying Multimedia into Learning Plan to Improve Table Tennis Serving and Receiving Skills of University Students - Liu , Jia (International Journal of Sociologies and Anthropologies Science Reviews, 2025)
Background and Aim: As is known, table tennis is a popular sport that not only enhances physical fitness but also exercises one’s cognitive reaction and other aspects. Moreover, table tennis has been a fundamental course in many universities nowadays in China and other countries. However, there is still a lack of systematic and comprehensive learning plans or teaching plans, especially for university students in the Chinese context. That will lead to a negative effect on students’ performance in table tennis skills. This study attained the objective of analyzing the magnitude of multimedia’s influence on the learning effect of receiving and serving skills in table tennis among college students by establishing the hypothesis of profitability, which was analyzed and achieved by comparing the performance of 60 university students in the experimental group and the control group in an 8-week pre-test and post-test. Materials and Methods: Before the experiment, the researcher interviewed several experts to obtain the current status of table tennis teaching and learning, and refined the new learning program incorporating multimedia instruction based on the experts’ recommendations. This study was Quasi-experimental research. The population was 240 students who had no training in base table tennis from the sports student club of Shenzhen University of Technology in the academic year 2023. Then, 60 college students were selected accidentally and divided into two groups by the matching method: control and experimental groups. Then, an 8-week experiment was conducted to compare the differences and effects of multimedia teaching with traditional teaching methods. The results were analyzed by an independent sample t-test and one-way ANOVA to figure out the effect of the application of multimedia in learning, serving, and receiving capabilities of table tennis via the values of t-test statistics. Results: There is a significant difference in the outcomes between the pre-test and post-test (t=0.159and-10.740, p<.001*) concerning the serving and receiving abilities of table tennis, which demonstrated that the multimedia learning plan has a great effect on students’ performance in serving and receiving skills. Conclusion: The result of the experiment is that the hypothesis is valid, and the learning program using multimedia (post-test) has a greater positive impact on students’ learning outcomes than the traditional learning program. Research outcomes will be capable to applied in other contexts with multimedia learning plans and promote the development of the physical education field.